Catalytic Combustion Of VOC In Air Stream Over Bimetallic Chromium Copper Supported On SICL4-Modified H-ZSM-5 Catalyst. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (IIUM Press, 2006)
The performance of chromium (Cr) and copper (Cu) on silicon tetrachloride modifiec H-ZSM-5 (SiCl4-z) catalyst in Voc combustion is reported.